Development of certain benzylidene coumarin derivatives as anti-prostate cancer agents targeting EGFR and PI3Kβ kinases - Lina M. A. Abdel Ghany; Tarek S. Ibrahim; Abdulrahman S. Alharbi; Mohamed S. Abdel-Aziz; Eman M. El-labbad; Mohamed Elagawany; Noha Ryad (Journal of Enzyme Inhibition and Medicinal Chemistry)
Novel coumarin derivatives were synthesised and tested for their cytotoxicity against human cancer cells (PC-3 and MDA-MB-231). Compounds 5, 4b, and 4a possessed potent cytotoxic activity against PC-3 cells with IC50 3.56, 8.99, and 10.22 µM, respectively. Compound 4c displayed cytotoxicity more than erlotinib in the MDA-MB-231 cells with IC50 8.5 µM. Moreover, compound 5 exhibited potent inhibitory activity on EFGR with IC50 0.1812 µM, as well as PI3Kβ inhibitory activity that was twofold higher than LY294002, suggesting that this compound has a dual EGFR and PI3Kβ inhibiting activity. Docking aligns with the in vitro results and sheds light on the molecular mechanisms underlying dual targeting. Furthermore, compound 5 decreased AKT and m-TOR expression in PC-3 cells, showing that it specifically targets these cells via the EGFR/PI3K/Akt/m-TOR signalling pathway. Simultaneously, compound 5 caused cell cycle arrest at S phase and induced activation of both intrinsic and extrinsic apoptotic pathways.